Hi…..

The elimination method is to add both equations together and eliminates one of the variables so that you can solve for the other one. Since none of your variables have the value (-5x and x) and (12y and –2y), you much decide which variable you want to eliminate and which one you want to solve. Thus, your two equations can be written as this:

One option:

-5x + 12y = 20

6x-12y = -36 (multiplying the equation “x-2y = -6” by 6so that you can eliminate the y variable)

----------------------

x = - 16

Plugging –16 for x into the first equation will give you:

-5(-16) + 12y = 20

-80 + 12y = 20

12y = -60

y = -5

Plugging x = -16 and y = -5 into the first equation to double check your work

-5(-16) + 12(-5) = 20

80 – 60 = 20

Second option:

-5x + 12y = 20

5x – 10y = -30 (multiplying the equation “x-2y = -6” by 5 so that you can eliminate the x variable)

------------------------

2 y = -10

y = -5

Plugging –5 into the first equation will give you

-5x + 12(-5) = 20

-5x – 60 = 20

-5x = 80

x = -16

Both options will give you the same answer. X = -16 and Y = -5

Hope this helps!

Vicki

Did you find this answer useful?